Time policies, urban policies and planning - Fernandes, José Alberto Rio (2015)
Over the past few decades, significant social and economic transformations had a relevant correspondence in processes of territorial complexification, urban fragmentation and spatial injustice. Literature and research shows that these processes have also a very important temporal dimension, associated to a transition from an industrial society of synchronized rhythms to more heterogeneous everyday experiences where more individualized timespace associations of a growing number of people are based on atypical agendas and working hours. This article, that is associated with the Urban-Net project Chronotope, profiting from its discussions and results, takes as central the relation between time policies, urban policies and planning, analyzing differences between Oporto/Portugal, Barcelona/Spain, Malmoe/Sweden and Toulouse/France.